Studying problems, not problematic usage: Do mobile checking habits increase procrastination and decrease well-being?. (May 2022) - Meier, Adrian
Most prior research on the effects of mobile and social media on well-being has worked from either the "technology addiction" or "screen time" approach. Yet these frameworks struggle with considerable conceptual and methodological limitations. The present study discusses and tests an established but understudied alternative, the technology habit approach. Instead of conflating mobile usage with problems (i.e., addictive/problematic usage) or ignoring users' psychological engagement with mobiles (i.e., screen time), this approach investigates how person-level (habit strength) and day-level aspects of mobile habits (perceived interruptions and the urge to check) contribute to a key problem outcome, procrastination, as well as affective well-being and meaningfulness. In a five-day diary study with N = 532 student smartphone users providing N = 2, 331 diary entries, mobile checking habit strength, perceived interruptions, and the urge to check together explained small to moderate amounts of procrastination. Procrastination, in turn, was linked to lower affective well-being and meaningfulness. Yet mobile habits showed only very small or no direct associations with affective well-being and meaningfulness. By separating habitual mobile connectivity from problem outcomes and well-being measures, this research demonstrates a promising alternative to the study of digital well-being.